Strategi Pengembangan Bukit Tinatar Pada Era Adaptasi Kebiasaan Baru Di Yogyakarta - Nur Rohman; Fernanda Primandaru Pratama (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
This research is important to know the development strategy of Bukit Tinatar in the era of adaptation of new habits in Yogyakarta. In addition, in Bukit Tinatar there is still a lot of potential that must be developed again by adjusting to the Covid-19 pandemic that is currently being experienced by the world. In this study the authors used qualitative research methods. The qualitative method according to Sugiyono (2017) is a descriptive research method that tends to use analytical methods, this method has a theoretical basis and can be used for better understanding, so that it can focus research based on what happened during observations. The results showed that Bukit Tinatar had several weaknesses, namely the lack of supporting facilities such as stall toilets and gazebos and inadequate road access and the lack of street lighting to get to the location. Therefore, it is necessary to make improvements and improvements so as not to make it difficult for tourists who come. In terms of further improving in terms of promotion which of course can use existing social media such as Instagram, Facebook, websites or other platforms.